Experience and perspectives of users and non-users of the Ask your pharmacist teleconsultation platform - Véronique Turcotte; Alexandre Chagnon; Line Guénette (Elsevier, 2021)
Background: There is a growing trend concerning the use of information and communication technologies (ICT) for seeking health-related information such as information on medications and side effects. However, people looking online for health information cannot always judge the credibility of the information. Objective(s): This study aimed to describe patients' and pharmacists' experience using an asynchronous teleconsultation platform entitled "Ask Your Pharmacist" (AYP) and gather their perspectives and those of various healthcare and social services professionals providing primary care. Methods: We performed semi-structured individual interviews over the telephone with patients having used the platform, pharmacists providing teleconsultation services on the platform, and various professionals delivering healthcare and psychosocial services to ambulatory patients. The questions explored specific themes, such as the perceived utility and impacts of the platform. We transcribed the interviews and performed a content analysis. Results: We interviewed eight patients, six AYP pharmacists, and 15 healthcare and social services professionals. Participants perceived that the platform was simple to use and accessible. They also perceived that AYP promoted the visibility and the value of pharmacists' services. Some constraints were also shared, notably regarding questions requiring immediate attention or about complex situations. Conclusions: The experience and perspectives of users and non-users of the AYP platform are mostly positive, but concerns were also raised regarding patients' safety. Results suggest that AYP could be a complementary tool to offer to ambulatory patients for simple, general and non-urgent problems.